When Angels Misbehaved: Justiciability of the United Nations for the Cholera Outbreak in Hait - Muhammet Celal Kul (İstanbul Hukuk Mecmuası)
The justiciability of international organizations has recently sparked considerable debate and interest. Among these comes the debate whether the United Nations (UN) was acting within its rights when hiding behind its immunity in the Cholera Outbreak in Haiti. Another point of contention is whether immunity is necessary vel non for the independence of the UN from member states, even in extreme cases where human rights are violated. In this paper, the justiciability of the UN is discussed over the concepts of immunity, autonomy, and responsibility of international organizations along with the moral obligations of the UN and the effective use of the alternative systems to compensate victims. The UN’s role resembles that of God, as He bears no responsibility for His actions besides being above law. Similarly, troops or personnel participating in UN operations are expected to work for the good of humanity, such as angels. Nevertheless, the UN angels sometimes commit violations or cause damage, which stimulates further discussion of the matter. To put these theoretical questions and metaphors into practice, the Cholera Outbreak in Haiti is chosen as it provides a contemporary example that is a developing story paving the way for understanding the immunity, responsibility, and justiciability of the UN. In this article, the immunity of the UN has been analyzed along with that of other international organizations to demonstrate the special position of the UN. Finally, a waiver of immunity was tested with some extreme examples in which violations of human rights and jus cogens norms were involved.